2004
DOI: 10.1254/jphs.94.177
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity and Antioxidant Status of Caesalpinia bonducella Against Ehrlich Ascites Carcinoma in Swiss Albino Mice

Abstract: Abstract. The methanol extract of Caesalpinia bonducella FLEMING (Caesalpiniaceae) leaves (MECB) were evaluated for antitumor activity against Ehrlich ascites carcinoma (EAC)-bearing Swiss albino mice. The extract was administered at the doses of 50, 100, and 200 mg / kg body weight per day for 14 days after 24 h of tumor inoculation. After the last dose and 18 h fasting, the mice were sacrificed. The present study deals with the effect of MECB on the growth of transplantable murine tumor, life span of EAC-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
192
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(215 citation statements)
references
References 22 publications
22
192
0
1
Order By: Relevance
“…The results indicate that MECB exhibited significant antitumor and antioxidant activity in EAC-bearing mice. 47 …”
Section: Caesalpinia Bonducellamentioning
confidence: 99%
“…The results indicate that MECB exhibited significant antitumor and antioxidant activity in EAC-bearing mice. 47 …”
Section: Caesalpinia Bonducellamentioning
confidence: 99%
“…The present study showed that EEAP significantly increased the life span than that of EAC control. The reliable criteria for judging the value of any anticancer drug are prolongation of life span and decrease of WBC count (Gupta et al, 2004). The results demonstrate the indirect inhibitory effect of the extract in EAC bearing group, which is probably mediated by the enhancement and deactivation of either macrophages or cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…23 Regarding this point, compound (2) has presented the best performance values, showing mean survival time superior to 90 days, equivalent to more than 100% of ILS, as with cis-DDP ( Table 2). …”
Section: Biological Activitiesmentioning
confidence: 94%
“…Based on the values of MST found we calculated the increase in life span (ILS). These parameters were calculated 23 …”
mentioning
confidence: 99%